Chemical characterization of pine bark (Pinus pinaster Aiton subsp. atlantica), antioxidant properties and phenolic profile of its extracts - Catarina da Silva Vieito; Preciosa Pires; Élia Fernandes; Manuela Vaz Velho (Millenium, 2019)
Introduction: Pine bark is an agroindustrial residue from the timber industry and represents a source of phenolic compounds. These compounds have several beneficial properties being antioxidants, antimicrobial, anti-inflammatory, cardiovascular, among others.